“More than just cleaning”: A qualitative descriptive study of hospital cleaning staff as patient caregivers - Nicole Vance; Kupiri Ackerman-Barger; Jann Murray-García; Fawn A. Cothran (International Journal of Nursing Studies Advances, 2022)
Background: Cleaning staff in hospitals can spend an average of 10–20 min per day per patient room. Published literature shows a pattern of interactions between housekeepers and patients, and that they believe themselves to be a part of the patient care team. To date, no study about this phenomenon has been done in the United States or has framed them through the lens of patient care. Objective: To describe the experiences and perceptions of hospital housekeeping staff in relation to patient care. Design: Qualitative descriptive. Setting: A 625-bed tertiary, academic medical center in the United States. Participants: Eight housekeeping staff participated, ranging from 40 to 62 years old, from diverse cultural and ethnic backgrounds, and worked at the study hospital from 4 months to 20 years. Interviews were conducted between September 2020-October 2020. Participants were recruited through flyers, email, and snowball sampling. Data were collected through semi-structured, in-depth interviews lasting 30 – 60 min. Data were analysed through thematic analysis using a 6-step framework that included data familiarization, generation of initial codes, search for themes, review of data, definition and naming of themes, and generation of a written report. Trustworthiness of the data was established through strategies such as reflective journaling, researcher triangulation and member-checking. Results: Three themes emerged: 1) “Here to take care of you” 2) Difficulties & Coping: and 3) Perceptions of their role. These three themes provide insight into participants' perceptions of patient interactions and the kind of connections they formed with patients as they went about their duties. Conclusions: Study findings suggest that there exists among housekeeping staff a respect for the humanity of patients, a duty to protect people from disease, and a longstanding practice of engaging in therapeutic connections with patients. As noted elsewhere, there remains a disparity between the importance of this role and the recognition and dignity afforded it. These results reveal an opportunity to expand our understanding of who we call a caregiver, and to improve how we recognize and support each member of the healthcare team.